Comparison of the Risk of Early Postoperative Infection and Length of Hospital Stay between Sarcopenic and Nonsarcopenic Adults Undergoing Live Donor Liver Transplantation Using Computed Tomography. - Yadav, Garima; Ganesan, Prem Kumar; Khadaria, Narottam; Chaudhary, Abhideep; Raj, Shashank (Indian Journal of Radiology & Imaging, 2026)
Objectives: Computed tomography (CT)-based sarcopenia assessment and the risk of early postoperative infection among adults undergoing live donor liver transplantation. This article also compares the postoperative length of hospital stay in sarcopenic and nonsarcopenic patients after live donor liver transplantation. Materials and Methods: Sixty live donor liver transplantation recipients undergoing abdominal CT scans were included during the period from April 2022 to February 2024. CT data was obtained via 128-slice Revolution Frontier CT by GE Healthcare. Individual vertebral levels were identified on CT scan and skeletal muscle cross-sectional areas were computed using MATLAB algorithms. SliceOmatic software aided in muscle area determination and L3 vertebra served as the reference for assessing abdominal muscles. Skeletal muscle index was derived by normalizing muscle area to height. Sex-specific sarcopenia cutoffs were applied based on CT findings. Postoperative care included surveillance for infections using blood culture positivity. Results: Note that 76.47% of the infected patients were sarcopenic while 23.53% were nonsarcopenic. Also, 32.56% of the noninfected patients were sarcopenic whereas 67.44% were nonsarcopenic (p -value = 0.003). Postop length of hospital stay in days showed a significant difference between the two groups (p ≤ 0.001), with the sarcopenic group having the greatest median postop length of hospital stay. Conclusion: Pretransplant sarcopenia as determined by skeletal muscle index is associated with an increased risk of posttransplant infections in a group of patients undergoing liver transplantation as well as longer stay in hospital.